Assessment of customer satisfaction of a restaurant in Santa Maria - RS - Moreira Junior, Fernando de Jesus; Oliveira, José Renê de; Ansuj, Angela Pellegrin; Weise, Andreas Dittmar (Revista de Administração da UFSM, 2019)
This paper aims to evaluate the satisfaction level of customers of a restaurant inSanta Maria- RS, using descriptive statistical analysis in order to identify opportunities for improvements to the rated restaurant. Customers were asked to rate, for each item, your satisfaction, according to a Likert scale. The results showed that the restaurant seems to meet customer expectations with respect to its internal structure, layout, accessibility, location, the options and the speed in payment and the price charged in addition to all aspects aspects related to food. However, it was found that the highest rates of dissatisfaction are related to the smell of the internal environment, parking and internal decoration. The results presented by this research, as well as recommendations for improvement will be forwarded to the restaurant so that necessary measures can be taken to ensure continuous improvement of the quality of their services.